The impact of nationality status and place of residency on health-related social needs and quality of life among Palestinian Refugees in Jordan - Hamza Alduraidi; Rahaf Issam Abu Zayid; Noor Mahmoud Jaber; Bassam Saleh Hijazi; Sa'ed Radwan Khamis; Hasan Fahed Awad; Marah Al-Khateeb; Saif alnour Mahmoud Aldhirat; Ahmad Amjed Toubasi (Heliyon)
Introduction: Large number of Palestinian refugees reside in Jordan; most of whom enjoy Jordanian citizenship, and most of whom reside outside camps. Poverty, unemployment, and a poor health profile are more prevalent among camp-residing refugees and non-citizen refugees. This study aims to assess differences in health-related social needs and quality of life among different Palestinian refugee communities in Jordan, based on their nationality status and camp residency. Methods: A descriptive, comparative, cross-sectional design was used to measure health-related social needs (using the Accountable Health Communities Health-related Social Needs (AHCHRSN) screening tool) and quality of life (using the World Health Organization Quality of Life BREF (WHOQOL-BREF)) among a sample of 236 adult Palestinian refugees in three contexts; (off-camp, in-camp citizens, and in-camp non-citizens) in Jordan. Results: All participants had needs in the mental health domain, and 179 (75.8 %) suffered from food insecurity. Living in Gaza and Husn camps correlated with increased odds of safety needs (OR = 4.27, 95%CI: 1.541 to 11.76 and OR = 2.936, 95%CI: 1.942 to 9.147) and financial needs (OR = 6.135, 95%CI: 2.062 to 18.181 and OR = 3.932, 95%CI: 1.765 to 8.210) compared to living outside camps. Gaza and Husn camps were associated with higher odds of employment needs (OR = 2.349, 95%CI: 1.877 to 6.291 and OR = 2.406, 95%CI: 1.050 to 5.514) compared to living outside camps. Quality of life scores did not vary significantly between participants in the three settings. Conclusion: Health-related quality of life scores are generally low across all Palestinian refugee communities. A Palestinian refugee who lives in Gaza camp is four times more likely to have safety needs, six times more likely to have financial needs, and over twice more likely to have employment needs than a refugee outside camps. Despite having citizenship, a Palestinian refugee who lives in Husn camp is three times more likely to have safety needs, four times more likely to have financial needs, and over twice more likely to have employment needs than a refugee outside camps. International states and organizations should help meet these needs by funding the United Nations’ Relief and Work Agency for Palestinian Refugees in the Near East (UNRWA) and the Jordanian government. Further research is needed to understand the lived experience of Palestinian refugees, and the impact of lacking citizenship and residing in camps on their lives and livelihoods, especially after the coronavirus disease 2019 (COVID-19) pandemic.